Immigration: Picking the low-hanging fruits - Kristian Niemietz (Institute of Economic Affairs (IEA), 2019)
Opinion surveys consistently show that the British public is hostile to immigration. However, if we dig a little deeper into the polling data, a more differentiated picture emerges. Despite overall hostility to immigration, there are types of immigration that are widely accepted, or even popular with the public. Contrary to the way the debate is usually framed, concerns about immigration are not really about overall numbers. Anxieties about immigration are primarily cultural, not economic. The net migration target should be abolished, as net migration levels are irrelevant. The cap on the number of work visas for highly skilled people (Tier 2 visas) should also be abolished. Skilled migration is popular with the public, and Tier 2 migrants are, almost by definition, highly productive economic and fiscal net contributors. Limiting their numbers is not just needless economic self-harm: it is not even good politics. The government should also make it easier for foreign students to come here, to work alongside their studies, and to work here after their studies. Debates about post-Brexit immigration policy options are predicated on the assumption that after Brexit, the UK must have one single immigration regime vis-à-vis the EU as a whole. This is not true. The UK could keep free movement with some countries, and end it for others. Free movement was never controversial in the UK before the 2004 EU enlargement. There is no reason why the UK should not be able to keep free movement for the old member states (the EU-14) and the EFTA countries. There is a two-thirds majority for free movement between Canada, Australia, New Zealand and the UK ("CANZUK"). This is a clear-cut example of where immigration policy can be liberalised with public support. Free movement between these countries should be introduced immediately, ideally on a reciprocal basis, or unilaterally if not. This could potentially be extended to other countries, if and when there is public support for it. Britain's future migration system should be a two-lane system. There should be free movement for some countries, although unlike in the past, those would not all have to be European countries. They would simply be the countries which the British public is most comfortable to share an open border with. For the rest of the world, there should be a simplified, uncapped version of the current tier system.
Keywords: F22; F15; J24; J11; F22; F15; J24; J11; 330